−(2x+5)=−10−2x
Step 1: Simplify both sides of the equation.
−(2x+5)=−10−2x
−2x+−5=−10+−2x(Distribute)
−2x−5=−2x−10
Step 2: Add 2x to both sides.
−2x−5+2x=−2x−10+2x
−5=−10
Step 3: Add 5 to both sides.
−5+5=−10+5
0=−5
Answer:
There are no solutions.
Answer:
0.01863, yes preference
Step-by-step explanation:
given that a class consists of 12 boys and 12 girls. The teacher picks five students to present their work to the rest of the class and says that the five students are being selected at random
Here selecting any 5 students from the group of total 24 students is combination because order does not matter.
Total no of ways of selecting any 5 from total 24 = ![24C5\\=42504](https://tex.z-dn.net/?f=24C5%5C%5C%3D42504)
No of ways of selecting only 5 girls = No of ways of selecting random 5 girls from total 12 girls
= ![12C5\\=792](https://tex.z-dn.net/?f=12C5%5C%5C%3D792)
a) the probability be that all five students
selected are girls=![\frac{792}{42504} \\=0.01863](https://tex.z-dn.net/?f=%5Cfrac%7B792%7D%7B42504%7D%20%5C%5C%3D0.01863)
b) Since the probability for selecting all girls is very small and near to 0, it is unusual to select all girls if done at random. Hence the teacher had a preference for girls.
Answer:
Recursive
a(1) = 9 ; a(n+1) = 3 * a(n)
Explicit
a(n) = 9 * 3^(n-1)
Answer:
μ ≈ 2.33
σ ≈ 1.25
Step-by-step explanation:
Each person has equal probability of ⅓.
![\left[\begin{array}{cc}X&P(X)\\1&\frac{1}{3}\\2&\frac{1}{3}\\4&\frac{1}{3}\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7DX%26P%28X%29%5C%5C1%26%5Cfrac%7B1%7D%7B3%7D%5C%5C2%26%5Cfrac%7B1%7D%7B3%7D%5C%5C4%26%5Cfrac%7B1%7D%7B3%7D%5Cend%7Barray%7D%5Cright%5D)
The mean is the expected value:
μ = E(X) = ∑ X P(X)
μ = (1) (⅓) + (2) (⅓) + (4) (⅓)
μ = ⁷/₃
The standard deviation is:
σ² = ∑ (X−μ)² P(X)
σ² = (1 − ⁷/₃)² (⅓) + (2 − ⁷/₃)² (⅓) + (4 − ⁷/₃)² (⅓)
σ² = ¹⁴/₉
σ ≈ 1.25
Answer:
The answer is option C
Step-by-step explanation:
f(x) = x³ + 2x² + 3x + 4
To find f(-1) substitute the value of x that's
- 1 into f(x)
That's
<h3>
![f( - 1) = ({ - 1})^{3} + 2 ({ - 1})^{2} + 3( - 1) + 4 \\ = - 1 + 2(1) - 3 + 4 \\ = - 1 + 2 - 3 + 4 \\ = 1 - 3 + 4](https://tex.z-dn.net/?f=f%28%20-%201%29%20%3D%20%20%28%7B%20-%201%7D%29%5E%7B3%7D%20%20%2B%202%20%28%7B%20-%201%7D%29%5E%7B2%7D%20%20%2B%203%28%20-%201%29%20%2B%204%20%5C%5C%20%20%3D%20%20-%201%20%2B%202%281%29%20%20-%203%20%2B%204%20%5C%5C%20%20%3D%20%20-%201%20%2B%202%20-%203%20%2B%204%20%5C%5C%20%20%3D%201%20-%203%20%2B%204)
</h3>
We have the final answer as
<h3>
![f( - 1) = 2](https://tex.z-dn.net/?f=f%28%20-%201%29%20%3D%202)
</h3>
Hope this helps you